Effect of tissue glue versus suture in pterygium surgery in a tertiary care center of North-East India - Deori, Monalisa; Kuli, J. J.; Boruah, Bharati D. (International Journal of Research in Medical Sciences, 2021)
Background: Pterygium is a triangular fibrovascular tissue of conjunctiva encroaching on to the cornea. Currently, conjunctival autograft technique after excision is reported as the most suitable and safest method. The autograft transplantation can be done either with the help of suture or tissue adhesives. Objective of the study was to evaluate the effects of tissue glue versus suture in limbal conjunctival autograft transplantation among the patients undergoing pterygium excision. Methods: A prospective study was carried out in a tertiary eye care hospital. 60 patients with primary pterygium underwent limbal conjunctival autograft transplantation. They were enrolled into two groups, group-A (tissue glue, N=30) and group-B (suture group, N=30). Operative time, postoperative patient comfort and recurrence of pterygium were assessed. The patients were followed-up for 6 months. Results: The mean surgical time in fibrin glue group (23.56±2.80) was significantly less compared to suture (30.78±2.20) group with p<0.001. Postoperative discomfort in terms of pain, lacrimation and foreign body sensation was significantly less with fibrin glue in comparison to suture (p<0.05). Postoperative complications like redness, subconjunctival hemorrhage, graft edema and graft retraction were significantly more in suture group during late postoperative period. Recurrence of pterygium was noted in two patients (6.67%) in suture group and one patient in fibrin glue group (3.33%) which was not statistically significant (p>0.005). Conclusions: The use of fibrin glue for securing the limbal conjunctival autograft in pterygium surgery significantly reduces the operating time and postoperative discomfort.